Expansionary monetary policy and bank lending: the case of new Euro Area member states. (20th September 2020) - Fisera, Boris; Kotlebova, Jana
We study the effectiveness of the bank lending channel in the transmission of the unconventional monetary policies of the European Central Bank (ECB). We use the bias-corrected LSDV estimator to study the effect of ECB's unconventional policies on bank lending to private sector on a sample of 54 banks from the 5 new Euro Area (EA) member states over the years 2008-2018. We distinguish two groups of unconventional monetary policies - the Quantitative Easing (QE) and central bank lending to commercial banks. We find that the two groups of unconventional policies did not have a statistically significant effect on bank lending in all the sampled countries. However, for Slovakia, with its comparatively healthy banking system, we find evidence that the QE did boost credit provision to private sector. Indeed, we find that both the ECB's lending to commercial banks and the QE had stronger effect on healthier banks in Slovakia.